INTERVENSI PROGRAM PEMBINAAN GABUNGAN KELOMPOK TANI OLEH BALAI PENYULUHAN PERTANIAN DI DESA KARANGAMPEL KECAMATAN BAREGBEG KABUPATEN CIAMIS - Komariah, Elis Nurul (Universitas Pahlawan Tuanku Tambusai, 2025)
This study is driven by the suboptimal implementation of interventions in the form of education, learning by doing/training, and self-monitoring in the development of Farmers Group Associations (Gapoktan) conducted by the Agricultural Extension Center (Balai Penyuluhan Pertanian) through Field Agricultural Extension Officer (Penyuluh Pertanian Lapangan) Karangampel Village, Baregbeg District, Ciamis Regency. The objective of this research is to examine how intervention strategies are applied in the depelopment of Farmers group associations by the agricultural extension center in the specified location. The study employs a descriptive qualitative method involing seven informants. Data were collected through literature review, documentation, field observation, and in-depth interviews. The data analysis process includes data collection, data reduction, and conclusion drawing or verification. The findings indicate that the intervention program implemented by the agricultural extension center in the development of Gapoktan has not been fully effective. This is evident from the inadequate monitoring componenr, which has not been carried out optimally by extension officers. One of the main inhibiting factors is the extensive coverage area, which hinders the ability of extension officers to regulary visit all farmer groups. Consequently, the development process is less effective, as extensionofficer are often unaware of the progress or challenges faced by the Gapoktan. As an effort to overcome this constaint, a regular visitions schedule has been devised based on a proritizationn of target areas.